Efficacy of Chinese herbal medicine in patients with osteoporosis: a systematic review and meta-analysis - Wang, Jin; Teng, Fei (Frontiers in Medicine, 2025)
IntroductionCurrent evidence from randomized controlled trials (RCTs) supports the anti-osteoporotic properties of Chinese Herbal Medicine (CHM); however, its therapeutic advantages over conventional treatments remain inconclusive. This study aimed to compare the therapeutic effects of CHM with those of conventional therapy in patients with osteoporosis, using a meta-analysis approach.MethodsA systematic search of PubMed, Embase, Cochrane Library, CNKI, and Wanfang databases was conducted through March 2025 to identify eligible RCTs. The weighted mean difference (WMD) and 95% confidence intervals (CI) were used as effect estimates, with pooled analyses calculated using a random-effects model. Additional exploratory analyses included sensitivity and subgroup analyses.ResultsEighteen RCTs involving a total of 1,816 patients with osteoporosis were included in the meta-analysis. CHM was associated with increased bone mineral density (BMD) at the lumbar spine (WMD: 0.09; 95% CI: 0.04 to 0.13; p < 0.001), femoral neck (WMD: 0.09; 95% CI: 0.02 to 0.17; p = 0.015), and Ward’s triangle area (WMD: 0.08; 95% CI: 0.01 to 0.15; p = 0.025). However, CHM showed no significant effect on BMD at the greater trochanter of the femur (WMD: 0.01; 95% CI: −0.03 to 0.05; p = 0.698). Additionally, CHM was not associated with changes in alkaline phosphatase (WMD: 0.98; 95% CI: −6.88 to 8.83; p = 0.808), serum calcium (WMD: 0.08; 95% CI: −0.09 to 0.25; p = 0.372), or serum phosphorus (WMD: -0.05; 95% CI: −0.22 to 0.12; p = 0.574).ConclusionChinese Herbal Medicine was associated with significant improvements in BMD at the lumbar spine, femoral neck, and Ward’s triangle area compared to conventional therapies, though the evidence is limited by moderate study quality and high heterogeneity. The findings suggest potential benefits of CHM in specific skeletal sites, but further rigorous trials are needed to confirm efficacy.Systematic review registrationINPLASY platform (number: INPLASY202530115).